1997
DOI: 10.7164/antibiotics.50.641
|View full text |Cite
|
Sign up to set email alerts
|

Stachybotrin C and Parvisporin, Novel Neuritogenic Compounds. II. Structure Determination.

Abstract: The structures ofstachybotrin C and parvisporin have been determined by spectroscopic analyses and chemical derivatization. Stachybotrin C contains a unique pyrano-isoindolinone ring system, while parvisporin has a hydroxyl farnesyl phenol structure. StachybotrinC and parvisporin are novel neuritogenic compounds isolated from the culture broth of Stachybotrys parvispora F4708. Their taxonomy, fermentation, isolation and physico-chemical properties were reported in the preceding paper1}. In this publication, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
22
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 0 publications
4
22
0
Order By: Relevance
“…The isoindolinone motif is not only a core structure in natural products such as daldinan A from the saprotrophic fungus Daldinia concentrica (Lee et al, 2012), stachybotrin C from the culture broth of Stachybotrys parvispora (Nozawa et al, 1997a;Nozawa et al, 1997b), lennoxamine from Berberis species (Fuchs and Funk, 2001), cichorine from Aspergillus silvaticus (Kawahara et al, 1988), fumaramidine from Fumaria parviflora (Hussain et al, 1981), and pestalachloride A from co-fermentation of a marine fungus and a marine bacterium (Li et al, 2008), but is also found in a number of pharmacologically relevant synthetic molecules such as (S)-PD 172938 (Belliotti et al, 1998), and ASK 186 (Kato et al, 1993;Lamblin et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…The isoindolinone motif is not only a core structure in natural products such as daldinan A from the saprotrophic fungus Daldinia concentrica (Lee et al, 2012), stachybotrin C from the culture broth of Stachybotrys parvispora (Nozawa et al, 1997a;Nozawa et al, 1997b), lennoxamine from Berberis species (Fuchs and Funk, 2001), cichorine from Aspergillus silvaticus (Kawahara et al, 1988), fumaramidine from Fumaria parviflora (Hussain et al, 1981), and pestalachloride A from co-fermentation of a marine fungus and a marine bacterium (Li et al, 2008), but is also found in a number of pharmacologically relevant synthetic molecules such as (S)-PD 172938 (Belliotti et al, 1998), and ASK 186 (Kato et al, 1993;Lamblin et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…The isoindolinone moiety is found in several natural products such as lennoxamine, [9] stachybotrine C, [10] pestalachloride A, [11] and taliscanine. [12] It is also the core structure of biologically active compounds, including as pagoclone, [13] chlorthalidone [14] and NU8165.…”
Section: Introductionmentioning
confidence: 99%
“…1) is important because the isoindolin-1-one substructure is common in a number of natural products and pharmaceuticals. [1][2][3][4][5] The isoindolin-1-one scaffold is of particular interest to medicinal chemistry because of its centrality in a variety of biologically active compounds and pharmaceutical target molecules. In particular, the N-benzyl substitution motif is a common structural variation (Fig.…”
Section: Introductionmentioning
confidence: 99%